Corporate Governance: Discussion - Анастасия Николаевна Степанова; Ольга Михайловна Иванцова (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2012)
Author: Anastasia N. Stepanova National Research University The Higher School of Economics, anstepanova@hse.ruIn this paper the authors review the working papers presented in 2011 at international conferences and workshops on corporate governance in Europe. The focus was made on the trends on corporate governance development in emerging markets and its influence over corporate performance. Besides, authors analyze the theoretical approaches to corporate governance that provoked a lot of discussion in 2011.